Suomen elintarviketeollisuuden työn tulevaisuus: Toimintaympäristöanalyysi - Martti Kulvik; Birgitta Berg-Andersson; Veera Nippala; Ilkka Kiema (The Research Institute of the Finnish Economy (ETLA), 2024)
– In this report, we present the current state of the Finnish food industry through statistics and propose perspectives on the future of the sector. We observe that although the wage level in the industry in Finland is relatively high compared internationally, productivity is also at a good level, resulting in good cost competitiveness. Finnish food industry is very domestically focused compared to other industries and benchmark countries. Despite lagging behind in profitability and research and development investments compared to other industries, internationally, the Finnish food industry performs excellently. The level of processing in Finnish food industry even surpasses that of benchmark countries. Interesting questions affecting the future of the food industry include changes in consumption habits, sustainability, climate change, geopolitical crises, obesity prevention, and general economic development. This overview is part of the Finnish Institute of Occupational Health's TYÖ2030 program, which encourages dialogue among stakeholders and industry representatives regarding the future of work in various sectors in Finland.
Keywords: L6; L66; 330; Food industry; Food export; Food production; Competitiveness; Industry review; Future work